Rehabilitation of Juvenile Offenders (and IV) (Journal of Parents and Teachers, 2025)
The article defines how the rehabilitation of minors is carried out, considering that behavior change is difficult and requires consistency, discipline, and effort from all parties involved. Additionally, rehabilitation can be physical (nutrition, hygiene, sleep, health, or exercise), psychological, or moral, all of which should be accompanied by medical care.
Keywords: rehabilitation; behavior; minors; discipline